Study and Operation of Effluent Treatment Plant: Rosin and Turpentine Oil Industry Bilaspur (Himachal Pradesh): A Case Study - Tanwar, Ashok Kumar (My University, 2008)
Any process in industry that uses fresh water will generate waste water or effluent with different contaminants. Over the past two decades the environment regulatory requirements has become stringent because of increased awareness of human health and ecological risk associated with the environment contaminants. One of the main causes for these contaminants is the industrial discharge from textiles industry, paper and pulp industry, rosin and turpentine oil industry, and many other chemical and pharmaceuticals industries, thus posing a threat to living beings. During M. Tech. thesis, I got the opportunity to work in Rosin and Turpentine oil industry. The concerned industry is located in Bilaspur (Himachal Pradesh). In that region, there are only two such industries. The project is concerned with the successful installation and operation of the ETP of the said industry. In the industry, rosin mix with soil and some turpentine oil are the main contaminants. In the project, complete study of the industry was done regarding all the point sources from where the waste and the effluent can be generated. To fulfill the above task, I understood all the processes with their inputs and outputs, and then ETP was installed, operated and maintained successfully. The ETP was operated and maintained as per the required conditions of the industry. Time to time analysis of the effluent has been done by measuring COD, BOD, pH, TDS etc. The ETP was maintained with repeated experimentation till the parameters under control as per pollution control board. Some new technologies are applied for solving the problems occurred at the time of successful operation of ETP.
M.Tech. (Environmental Sciences and Technology)
Keywords: Treatment; Rosin; Turpentine